Problem-Based Learning to Enhance Mathematical Communication Skills and Learning Outcomes in Graade V - Wahyuni, Lin; Sarwanto, Sarwanto; Atmojo, Idam Ragil Widianto (Universitas Sebelas Maret, 2024)
The implementation of the Problem-Based Learning model can improve the learning outcomes in mathematics regarding the volume of rectangular prisms and cubes among fifth-grade students at Elementary School. This study employs the Classroom Action Research method in an elementary school in the Yogyakarta region.. This is evidenced by the increased learning outcomes of the students in mathematics during Cycle I, which was 83.3%, and Cycle II, which was 86.3%. In Cycle I, the average score of the students in the first meeting was 73, and in the second meeting, it was 72. In Cycle II, the score in the first meeting was 80, and in the second meeting, it increased to 91. Problem-based learning significantly enhances the learning outcomes in mathematics and mathematical communication skills of the fifth-grade students a Elementary School. The implementation of the Problem-Based Learning model is carried out through five steps. The application of the Problem-Based Learning model can improve the learning outcomes and mathematical communication skills. This is evidenced by the observed improvement in the students' mathematical communication skills in each cycle. The average observation results in Cycle I were 75.84%, and in Cycle II, it increased to 86%.